Estrategias de marketing digital para la internacionalización de una app de cuidado de mascotas. - Ludeña Navarro, Esthela Elizabeth (My University, 2021)
ANIPAL is a mobile application (APP), which is based on the care and protection of pets. It also helps the animals of the city where the pet is located. The APP has all the necessary records and information regarding the pet and the owner, giving a new mobile application proposal. The purpose of this research will be to establish digital marketing strategies to internationalize the APP, the methodology is descriptive, in addition to an observation work, including digital marketing as a tool to internationalize and allow to establish the most suitable and correct market and introduce it to the market potential. The general objective of this work is to establish Digital Marketing strategies for the internationalization of the application.
ANIPAL es una aplicación móvil (APP), que se basa en el cuidado y protección de mascotas. También ayuda a los animales de la ciudad donde se encuentre ubicada la mascota. La APP cuenta con todos los registros e información necesaria referente a la mascota y al propietario, dando una propuesta de aplicación móvil novedosa. El propósito de la presente investigación será establecer estrategias de marketing digital para internacionalizar la APP, la metodología es descriptiva, además de un trabajo de observación, incluyendo al marketing digital como herramienta para internacionalizar y permitir establecer el mercado más idónea y correcta e introducirla al mercado potencial. El objetivo general de este trabajo es establecer estrategias de Marketing Digital para la internacionalización de la aplicación.
Keywords: MARKETING INTERNACIONAL; MARKETING DIGITAL